Aesthetics of Hui Folk Dance as audience service to leverage audience satisfaction / Chunyang Wu ... [et.al.] - Wu, Chunyang; Abu Bakar, Muhammad Fauzan; Boo, Ho Voon (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Hui folk dance has its unique charm as an indispensable part of Chinese folk dance. It reflects the customs and cultural characteristics of the Hui nationality. This article explores the historical formation of Hui folk dance, analyses its formation process in different periods of history, analyses the culture, the body vocabulary of the folk dance, the music, the rhythm of the dance, the influence on the folk dance, and the expression of aesthetic consciousness. Folk dances of the Hui nationality originate from the folk, and they also show their unique living habits, combining dance with the details of life to outline their unique dance posture. Hui folk dance expresses the value of aesthetic emotions, aesthetic knowledge, and aesthetic ideals of dance through historical portraits, national spirits, and traditional canons. The formation, aesthetic consciousness, and aesthetic characteristics of Hui folk dance were analysed to better understand the history and culture of Hui folk dance, learn it, inherit it, promote it, and enrich it for sustainability. Dance aesthetics as part of audience service. The audience will be aesthetically satisfied and this will affect their behavioural intentions.